Integrating Network Pharmacology and Experimental Validation to Investigate the Mechanisms of Huazhuojiedu Decoction to Treat Chronic Atrophic Gastritis. (7th December 2020) - Hao, Xinyu; Liu, Yu; Zhou, Pingping; Jiang, Qian; Yang, Zeqi; Xu, Miaochan; Liu, Shaowei; Zhang, Shixiong; Wang, Yangang
Abstract : Background . Chronic atrophic gastritis (CAG) is an important stage in the normal gastric mucosa's transformation into gastric cancer. Huazhuojiedu decoction (HZJD), a Chinese herbal preparation, has proven clinically effective to treat CAG. However, few studies have explored the mechanism of HZJD in CAG treatment. Purpose . This study aimed to shed light on the mechanisms underlying HZJD decoction CAG treatment using a network pharmacology approach and experimental validation. Methods . The active components of HZJD decoction were obtained from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform. Their targets were predicted through the SwissTargetPrediction database. Disease targets were screened using the GeneCards database. The disease and drug prediction targets were intersected to select the common potential therapeutic targets, which then were input into the Search Tool for the Retrieval of Interacting Genes to build a protein-protein interaction network. The "herb-compound-target-disease" and the "herb-target-pathway" network diagrams were constructed in Cytoscape 3.3.0. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis of effective targets were performed using the Database for Annotation, Visualization, and Integrated Discovery. Finally, the core targets were preliminarily verified by CAG rat model. The gastric mucosa's histopathological changes were observed via hematoxylin-eosin staining. The expressions of MAPK1, AKT1, TNF, VEGFA, and EGFR were detected by western blot and quantitative real-time reverse transcription-polymerase chain reaction. Results . A total of 155 nodes, including 20 putative targets of HZJD decoction, were selected as core hubs based on topological importance and were closely associated with the regulation of cell proliferation, apoptotic process, and cancer-related pathways (AKT1, TNF, VEGFA, and EGFR) in CAG. Further animal experiments showed that the expression of AKT1 in CAG rats was significantly increased, which was suppressed by HZJD decoction. TNF and VEGFA expression increased in the model group, but did not change in the HZJD group. MAPK1 and EGFR expression showed no significant differences among control, model, and HZJD groups. Conclusion . Taken together, the results suggest that the components of HZJD decoction can alleviate and prevent the severity of gastric precancerous lesions via AKT1 inhibition in CAG.